The Analysis of Compensation and Training Effect on Work Motivation with The Work Environment as An Intervening Variable at The Airport Authority Region II Office Medan - Maharani Ika Putri, Ratna; Robain, Wilchan; Rahayu, Sri (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to analyze the effect of compensation and training on work spirit with the work environment as an intervening variable at the Medan Airport Authority Region II. The employee population is 96 employees. The research model is path analysis and research data collection using a questionnaire. The results of the study are as follows: Employee compensation has a positive and significant effect on the work environment. Employee training has a positive and significant effect on the work environment. Employee compensation has a positive and significant effect on employee spirit. Employee training has a positive and significant effect on employee spirit. The work environment has a positive and significant effect on employee spirit. Employee compensation has a positive and significant effect on employee spirit through the work environment. Employee training has a positive and significant effect on employee spirit through the work environment. Training that is in accordance with the work, duties and responsibilities of employees who are encouraged by a comfortable work environment will foster high morale in employees to provide maximum work results so that agency goals can be achieved as well as possible. That employee training and the work environment have a mutually reinforcing relationship, where a good work environment will encourage agency leaders to carry out good employee training as well, which will ultimately create high enthusiasm among employees to provide maximum work results for Airport Authority Region II Medan. duties and responsibilities of employees who are encouraged by a comfortable work environment will foster high morale in employees to provide maximum work results so that agency goals can be achieved as well as possible. That employee training and the work environment have a mutually reinforcing relationship, where a good work environment will encourage agency leaders to carry out good employee training as well, which will ultimately create high enthusiasm among employees to provide maximum work results for Airport Authority Region II Medan. duties and responsibilities of employees who are encouraged by a comfortable work environment will foster high morale in employees to provide maximum work results so that agency goals can be achieved as well as possible. That employee training and the work environment have a mutually reinforcing relationship, where a good work environment will encourage agency leaders to carry out good employee training as well, which will ultimately create high enthusiasm among employees to provide maximum work results for Airport Authority Region II Medan.